2006
DOI: 10.1088/0026-1394/43/1a/06005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the standards for absorbed dose to water of the PTB, Germany and the BIPM for 60Co γ rays

Abstract: A comparison of the standards for absorbed dose to water of the Physikalisch-Technische Bundesanstalt (PTB), Germany and of the Bureau International des Poids et Mesures (BIPM) has been made in 60Co gamma radiation under the auspices of the key comparison BIPM.RI(I)-K4. The comparison result, based on the calibration coefficients for three transfer standards and expressed as a ratio of the PTB and the BIPM standards for absorbed dose to water, is 0.9961 (0.0037). This result replaces the earlier PTB value in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, both calorimetry systems have been compared to the primary standard operated at the BIPM and are in mutual agreement within 0.1%. 32 Comparing the beam output of the open=rotational mode (test B) to the static output (test A) differences are found within 0.2%, except for the UCL site where a difference of 1.3% is observed. The reason for this deviation remains unclear and could be attributed to either a limited statistics or to some yet unknown operational situation; the tomotherapy HiArt machine at this site belongs to a first generation system.…”
Section: Resultsmentioning
confidence: 89%
“…However, both calorimetry systems have been compared to the primary standard operated at the BIPM and are in mutual agreement within 0.1%. 32 Comparing the beam output of the open=rotational mode (test B) to the static output (test A) differences are found within 0.2%, except for the UCL site where a difference of 1.3% is observed. The reason for this deviation remains unclear and could be attributed to either a limited statistics or to some yet unknown operational situation; the tomotherapy HiArt machine at this site belongs to a first generation system.…”
Section: Resultsmentioning
confidence: 89%
“…A recent review of the different methods to measure photon absorbed dose can be found in the literature [1]. Some of the NMIs use water calorimetry (METAS-Switzerland, NIST-USA, NRCC-Canada, PTB-Germany, VSL-Netherlands [2][3][4][5][6][7][8][9][10]) and others use graphite calorimetry (BIPM, ARPANSA-Australia, BEV-Austria, ENEA-INMRI-Italy, NMIJ-Japan, NPL-United Kingdom, VNIIFTRI-Russia [11][12][13][14][15][16][17][18][19][20][21][22][23][24]).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous line indicates the average value of the ratio. The ratio of the D W primary standards of the PTB and the BIPM of 0.9961 [19] is indicated by the thick, dashed line; the standard uncertainty of this ratio of 0.0037 is represented by the thin dashed lines.…”
Section: Resultsmentioning
confidence: 99%
“…Nine detectors consisting of four alanine pellets each were irradiated in the 60 Co reference beam at the BIPM. The doses Dashed, thick line: ratio of the primary standards for absorbed dose to water of the PTB and BIPM [19]. The thin dashed lines indicate the standard uncertainty of the primary standard ratio.…”
Section: Discussionmentioning
confidence: 99%